The Association between Prolonged Antibiotic Use in Culture Negative Infants and Length of Hospital Stay and Total Hospital Costs - Sourour, Wesam; Sanchez, Valeria; Sourour, Michel; Burdine, Jordan; Lien, Elizabeth Rodriguez; Nguyen, Diana; Jain, Sunil K. (American Journal of Perinatology, 2021)
Objective This study aimed to determine if prolonged antibiotic use at birth in neonates with a negative blood culture increases the total cost of hospital stay.Study design This was a retrospective study performed at a 60-bed level IV neonatal intensive care unit. Neonates born <30 weeks of gestation or <1,500 g between 2016 and 2018 who received antibiotics were included. A multivariate linear regression analysis was conducted to determine if clinical factors contributed to increased hospital cost or length of stay.Results In total, 190 patients met inclusion criteria with 94 infants in the prolonged antibiotic group and 96 in the control group. Prolonged antibiotic use was associated with an increase length of hospital stay of approximately 31.87 days, resulting in a $69,946 increase in total cost of hospitalization.Conclusion Prolonged antibiotics in neonates with negative blood culture were associated with significantly longer hospital length of stay and increased total cost of hospitalization.Key Points
Keywords: prolonged antibiotic use; length of stay; total hospital cost; antibiotic stewardship